Effectiveness of Metal Coating Using Electroplating, Electroless Plating and Hot Dipping in the Manufacture of Weapons - Kostrada, Andhika; Jupriyanto, Jupriyanto; Siahaan, Timbul; Gultom, Rudy; Ramadhan, Muhammad Taufiq (International Journal of Social Service and Research, 2023)
The process of coating weapons is important in the manufacture of weapons, because it can improve the quality, durability and corrosion resistance of these weapons. Metal coatings on weapons can protect the surface of the weapon from damage due to friction, corrosion and other environmental effects. In addition, metal plating can also enhance the visual appearance of the weapon, giving the weapon an attractive and aesthetic appearance. Coatings can also increase the durability of weapons against various environmental conditions and extreme temperatures. The process of coating weapons must be done carefully and requires a complex process and requires proper handling. Therefore, the choice of the right coating method is very important in the manufacture of weapons, because it can affect the quality and durability of these weapons. There are several metal coating methods that can be used in the manufacture of weapons, including electroplating, electroless plating, and hot dipping. The method used is done by collecting and analyzing data from sources such as journals, notes, articles, reports, and other materials related to metal plating using electroplating, electroless plating and hot dipping. In this study, the results obtained that electroplating coating is a coating process that is suitable for the defense industry, because it has several characteristics that electroplating has in the process of coating weapons, due to the need for weapons from resistance due to wear and corrosion, this can be a recommendation to the parties. the defense industry in the process of coating the metal of these weapons uses the electroplating process today.